2012
DOI: 10.5923/j.nursing.20120201.01
|View full text |Cite
|
Sign up to set email alerts
|

Findings From a Quantitative Approach of Nurses Possibly Related to the Nursing Shortage Before Policy Modification in Macao

Abstract: The purpose of the present survey was to determine agreement levels among Macao nurses in the public sector on 57 items that could be related to the nursing shortage in Macao. An earlier qualitative inquiry showed that nurses working in the public health sector there had strong concerns about the number of nursing staff. Such a situation might decrease the likelihood of delivering quality care. A quantitative approach was used to assess the degree to which nurses agreed with the 57 items. These questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…Findings were contradictory with the study conducted by Leong were almost all (91.0%) agree that they are easily exhausted by workload. 10 Similar findings were reported in study by Mersin that revealed strong agreement on staff shortage, unfixed nurse patient ratio are causes of workload and weak health, frustration and easy exhausted are effects from workload. 21 The finding of current study showed that half of the respondents (50%) strongly agree that they are dissatisfied as their salary doesn't reflect their education qualification.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Findings were contradictory with the study conducted by Leong were almost all (91.0%) agree that they are easily exhausted by workload. 10 Similar findings were reported in study by Mersin that revealed strong agreement on staff shortage, unfixed nurse patient ratio are causes of workload and weak health, frustration and easy exhausted are effects from workload. 21 The finding of current study showed that half of the respondents (50%) strongly agree that they are dissatisfied as their salary doesn't reflect their education qualification.…”
Section: Discussionsupporting
confidence: 83%
“…Similar findings were reported in study by Leong which showed nearly two third (63.3%) of the respondents strongly agree that their workload increase due to inadequate nurses during staff shortage. 10 Majority (82%) of the respondents strongly agree that their workload increases due to unfixed nurse patient ratio. Similar findings were reported in study by Leong were almost all (95.7%) strongly agreed that their workload increases due to unfixed nurse patient ratio.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations